The neuromuscular, biochemical, endocrine and mood responses to small-sided games training in professional soccer. - Liam Kilduff (Journal of Strength and Conditioning Research, 2018)
The 24h responses to small-sided games (SSG) soccer training were characterized. Professional soccer players (n=16) performed SSG’s (4vs4 + goalkeepers; 6x7-min, 2-min inter-set recovery) with performance (peak-power output, PPO; jump height, JH), physiological (blood creatine kinase: CK, lactate; salivary testosterone, cortisol), and mood measures collected before (baseline), and after (immediately; 0h, +2h, +24h). For PPO and JH, possibly small-moderate reductions occurred at 0h (-1.1W·kg-1; ±0.9W·kg-1, -3.2cm; ±1.9cm, respectively), before returning to baseline at +2h (trivial) and declining thereafter (small-moderate effect) at +24h (-0.9W·kg-1; ±0.8W·kg-1, -2.5cm; ±1.2cm, respectively). Lactate increased at 0h (likely-large; +1.3mmol·L-1; ±0.5mmol·L-1), reduced at +2h (likely-small; -0.5mmol·L-1; ±0.2mmol·L-1), and returned to baseline at 24h (trivial). A very-likely small increase in CK occurred at 0h (+97u·L-1; ±28u·L-1), persisting for +24h (very-likely small; +94u·L-1; ±49u·L-1). Possibly-small increases in testosterone (+20pg·ml-1; ±29pg·ml-1) occurred at 0h, before likely-moderate declines at +2h (-61pg·ml-1; ±21pg·ml-1) returning to baseline at +24h (trivial). For cortisol, possibly-small decreases occurred at 0h (-0.09ug·dl-1; -±0.16ug·dl-1), before likely-large decreases at +2h (-0.39ug·dl-1; ±0.12ug·dl-1), which persisted for 24h (likely-small; -0.12ug·dl-1; ±0.11ug·dl-1). Mood was disturbed by SSG’s at 0h (likely-moderate; +13.6AU, ±5.6AU) and +2h (likely-small; +7.9AU; ±5.0AU), before returning to baseline at +24h (trivial). The movement demands of SSG’s result in a bimodal recovery pattern of neuromuscular function and perturbations in physiological responses and mood for up to 24h. Accordingly, when programming soccer training, SSG’s should be periodized throughout the competitive week with submaximal technical/tactical activities.